2021
DOI: 10.3389/fpsyt.2021.714301
|View full text |Cite
|
Sign up to set email alerts
|

Latent Profile of Internet and Internet Game Usage Among South Korean Adolescents During the COVID-19 Pandemic

Abstract: Introduction: Globally, more people are spending time on the Internet and gaming since the outbreak of the Coronavirus Disease 2019 (COVID-19). Consequently, concerns about developing behavioral addiction of adolescents have been raised. Such risk could be greater for adolescents in South Korea where the majority of adolescents have access to the Internet and own a smartphone. In fact, statistics indicate that Korean youths are spending significantly more time on the Internet and gaming during the COVID-19 pan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 66 publications
1
16
0
2
Order By: Relevance
“…The impact of COVID-19 on gaming disorder was examined in two aspects: whether game usage time increased and whether game addiction (e.g., IGD) scores measured on a game addiction scale increased during COVID-19. Several studies found increased game usage time and increased levels of game addiction ( 42 , 47 , 48 , 56 ). Among 18 articles, seven presented prevalence estimates of game addiction using scales, and three additional articles presented specific gaming hours.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The impact of COVID-19 on gaming disorder was examined in two aspects: whether game usage time increased and whether game addiction (e.g., IGD) scores measured on a game addiction scale increased during COVID-19. Several studies found increased game usage time and increased levels of game addiction ( 42 , 47 , 48 , 56 ). Among 18 articles, seven presented prevalence estimates of game addiction using scales, and three additional articles presented specific gaming hours.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding gender, males reported longer game usage time (44,45,47,48,51,56) and higher scores of game addiction than females (45,47,48,51,56). As loneliness played a significant role as a mediator (56) in females with higher scores of game addiction and increased scores of game addiction were reported in those who excessively used smartphones, the mechanism of using games might be different based on gender.…”
Section: Gaming Disorder According To Demographic Characteristicsmentioning
confidence: 99%
“…Nine studies reported the prevalence of GD during the early stages of the COVID-19 pandemic as follows: 11 percent among Vietnamese adolescents, 81 19 percent among Italian children and adolescents, 82 5.3 percent among Chinese children and adolescents, 83 16.6 percent among Spanish university students, 84 2.5 percent among medical students in Malaysia, 85 4.1 percent among Japanese middle-aged adults (8.5 percent among younger than 30), 77 15 percent among Chinese adolescents, 86 8.5 percent in college students from Nepal, 87 and 4.5 percent among Malaysian university students. 88 The 11 studies conducted on children and adolescent GD were associated with: age (i.e., being adolescent), 79,82,89 gender (i.e., being male), [82][83][84]86,[89][90][91][92] maladaptive coping regulatory styles, 86 poor social support, 83,86,89 depressive and anxiety symptoms before the COVID-19 pandemic, 76,92 poor mental health, 83 academic stress, 86 unhealthy parental care styles, [81][82][83] addictive gamer profile, 90,91 and excessive use of social networks. 84 With regard to adults, eight studies showed an increased risk of developing GD symptoms in association with age (i.e., being younger than 30 years), 77,79 gender (i.e., being male), 79,87 loneliness, 79,93 maladaptive self-regulation style,…”
Section: Study Outcomesmentioning
confidence: 99%
“…Concerning the nationality, the majority of the studies recruited participants who were residents on the European continent, especially Italy 54,82,95 and the United Kingdom, 18,79,80 North America (i.e., the United States), 17,20,[78][79][80] and Asia. 15,83,85,86,[90][91][92] Most of the studies (n = 11) recruited young adults (i.e., 18-35 years), 5 studies children (i.e., younger than 12 years old), 10 studies adolescents (i.e., 12-18 years old), 5 studies middle-aged adults (i.e., 36-55 years old), while no studies recruited older adults (i.e., up to 55 years old).…”
Section: Principal Findingsmentioning
confidence: 99%
“…Studi ini menunjukkan ukuran prevalensi gamer yang adiksi sebesar 1,2 persen (André et al, 2021). Di Korea Selatan persentase yang signifikan dari remaja ini melaporkan bahwa waktu mereka dihabiskan untuk game PC (45,5%) dan game seluler (56,6%) meningkat setelah wabah COVID-19 (Kim et al, 2021). Proporsi remaja yang adiksi video game adalah 16% (Saquib et al, 2017).…”
Section: Pendahuluanunclassified